Development of 3-DOF wrist mechanism for electro-hydrostatically driven robot arm. (17th July 2020) - Suzuki, Ryoya; Komagata, Mitsuo; Ko, Tianyi; Murotani, Kazuya; Kaminaga, Hiroshi; Tatano, Mamoru; Yamamoto, Ko; Nakamura, Yoshihiko
Abstract : Electro-hydrostatic actuator (EHA) has backdrivability and is suitable for a robot system that cooperates with human. However, its design methodology to miniaturize and to generate high pressure has not been established. We develop a robotic arm, all joints of which are actuated by EHAs. This paper reports the development of the vane motor type EHA and a wrist mechanism using the EHA. We employ a single vane motor for a wide motion range. In order to suppress internal leakage, we carefully set the clearance of the EHA and made the rigid casing by using ceramics disks. It is confirmed that the internal leakage of the new EHA is significantly reduced compared to that of the previous model. The wrist mechanism has three degrees of freedom, consisting of three vane motors in series. The flow path between a hydraulic pump and a vane motor is designed using metal pipings, swivel joints and manifolds are presented for a compact wrist mechanism. We validated the fundamental performance of the developed wrist mechanism through experiments. GRAPHICAL ABSTRACT: UF0001